A Study of Anatomical Shape of arch projected by Alveolar Process of Maxillary and Mandibular Bone - Baral, Prakash; Shrestha, Rami; Sapkota, Subash; Koju, Sapana; Chaudhari, Binod (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: Maxilla and Mandible have an alveolar process that bears socket for root of teeth. When the teeth fall or gets extracted there is resorption of alveolar process. The teeth alignment determines the shape of alveolar process. The objectives of the study was to assess the distribution pattern of anatomical shape of arch projected by alveolar process in Maxilla and Mandible and to compare the anatomy of arch amongst the population of Aryan and Mongoloid communities.Methodology: A total number of 856 people with intact anatomy of alveolar arch were included in the study. Anatomy of alveolar arches were assessed and noted for all. The brass wire was contoured according the shape of alveolar arch of patients and the shape was observed and noted down.Result: The study result showed there was significant difference in frequency distribution of ‘U’, ’V’ and ‘Ovoid’ shape alveolar arch form in maxilla and mandible. There was significant difference in distribution of ‘U’ and ‘V’ shape alveolar arch form in maxilla and ‘U’, ‘V’ and ‘Ovoid’ shape arch form in mandible between mongoloid and Aryan communities.Conclusion: ‘U’shape alveolar arch was seen more frequently in mandible where as “V” shape and ‘Ovoid’ shape arch in maxilla. ‘U’ shape alveolar arch was more frequently seen in Mongoloid communities and ‘V’ shape was more frequently seen in Aryan communities. There was no significant difference in comparison of frequency percentage of various types of arch form between the Male and Female.